Контроллеры простых точных идеалов групповых алгебр абелевых групп без кручения конечного ранга - Тушев, А.В. (Видавничий дім "Академперіодика" НАН України, 2007)
We develop some methods which allow studying properties of the controller of a faithful prime ideal I of the group algebra kA of a torsion-free Abelian group A of ﬁnite rank over a ﬁeld k. We apply some results of the theory of ﬁelds such as the Kummer theory and properties of the multiplicative groups of ﬁelds. Using these methods, in particular, we obtain an independent proof of a new version of the Brookes theorem on the controllers of prime ideals of the group algebra kA.